Assar Lindbeck. La economía política de la nueva izquierda. Madrid : Alianza Editorial, 1973. 227 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1974)
Assar Lindbeck, La economía política de la nueva izquierda, Madrid, Alianza Editorial, 1973.